Digital Media in Arabic Language Learning: Strengthening Communicative Competence in Indonesian Higher Education - Usfiyatur Rusuly; Jumriyah Jumriyah; Mubasyiroh Mubasyiroh (Abjadia : International Journal of Education, 2026)
This study investigates the role of digital media in Arabic language learning, particularly examining how digital literacy transitions into communicative competence. In the contemporary digital era, technology integration is essential for enhancing instructional effectiveness and efficiency. Despite its potential, challenges in implementing digital media within Arabic language education remain underexplored. Using a descriptive qualitative method with a case study approach, the research was conducted at the Language Development Center (PPB) of Maulana Malik Ibrahim State Islamic University (UIN) Malang. Participants included lecturers from the Arabic Language Education Study Program (PKPBA) and students from classes SY 1, HM 1, and TR 1. Data were collected through in-depth interviews and direct classroom observations guided by structured interview and observation instruments. The data were then analyzed thematically to identify patterns related to digital media usage in Arabic instruction. Findings reveal that digital media significantly increases student interactivity, participation, and motivation. Technology-supported learning environments encourage more dynamic communication practices, supporting the development of communicative competence. However, challenges persist, particularly regarding unequal access to technology and lecturers’ readiness to integrate digital tools effectively. The study concludes that digital media holds substantial potential to enhance Arabic communicative competence when supported by proper infrastructure and professional development. It recommends systematic lecturer training and improved technological facilities to optimize digital media-based Arabic learning.